Does parental angling selection affect the behavior or metabolism of brown trout parr? - Prokkola Jenni M; Alioravainen Nico; Mehtätalo Lauri; Hyvärinen Pekka; Lemopoulos Alexandre; Metso Sara; Vainikka Anssi (WILEY, 2025)
The behavior of organisms can be subject to human-induced selection such as that arising from fishing. Angling is expected to induce mortality on fish with bold and explorative behavior, which are behaviors commonly linked to a high standard metabolic rate. We studied the transgenerational response of brown trout (Salmo trutta) to angling-induced selection by examining the behavior and metabolism of 1-year-old parr between parents that were or were not captured by experimental fly fishing. We performed the angling selection experiment on both a wild and a captive population, and compared the offspring for standard metabolic rate and behavior under predation risk in common garden conditions. Angling had population-specific effects on risk taking and exploration tendency, but no effects on standard metabolic rate. Our study adds to the evidence that angling can induce transgenerational responses on fish personality. However, understanding the mechanisms of divergent responses between the populations requires further study on the selectivity of angling in various conditions.